Penjadwalan Perkuliahan Dengan Metode Vertex Graph Coloring Dan Simulated Annealing - Anggi Natanael Silitonga; Dicky Apdillah (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2017)
In college, lecture scheduling is very important in lecturing process, because the activities of lecturers and students depend on lecture schedule. To solve the problem, use Vertex GraphColoring and Simulated Annealing. In Vertex Graph Coloring, look for neighboring and neighboring vertices. While on Simulated Annealing, look for space and exchange positions randomly. The merger of Vertex Graph Coloring and Simulated Annealing aims to create optimum lecture schedule by looking at hard constraint and soft constraint. Testing is done at Faculty of Pharmacy University of North Sumatra, by making schedule from manual to computerized, so it is expected to make the schedule optimally and able to avoid hardconstaint and soft constraint.